UPAYA PENANGGULANGAN ALIH FUNGSI LAHAN PERTANIAN DENGAN PEMBERDAYAAN KRAMA SUBAK - Ni Putu Dyah Novi Lestari; Arwanto Harimas Ginting (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2021)
Subak is a traditional organization in the field of agriculture and irrigation of rice fields in indigenous peoples in Bali that is socioeconomic, religious, economical that historically continues to grow and develop and has been awarded World Cultural Heritage status by UNESCO on June 29, 2012. However, along with the development of the times, the conversion of agricultural land functions are increasing which results in agricultural land continues to decrease and the existence of Subak is increasingly threatened. This research uses the foundation of Empowerment Theory according to Totok Mardikanto. The research method used is qualitative research with descriptive method. Data collection techniques used in this study are by observation, interview, and documentation. While data analysis used in processing the data obtained is by data reduction, data display, and conclusion drawing. The observations showed that the empowerment process for Krama Subak has been running well but there are still obstacles that cause conversion of agricultural land function to continue to occur, such as the resources of heterogeneous farmers, farmers not owners of agricultural land, and farmers who are still tempted by rising land prices. Efforts made in addressing this is by holding the Hita Lalu Program, improving the intensification of subak administrators as well as the preparation of the Regulation on Sustainable Food Agricultural Land (LP2B). Keywords: Empowerment, Agriculture, Krama Subak